2014
DOI: 10.1177/1059601114560062
|View full text |Cite
|
Sign up to set email alerts
|

Building Employee Relationships Through Corporate Social Responsibility

Abstract: We explore the role of deeply held beliefs, known as social axioms, in the context of employee-organization relationships. Specifically, we examine how the beliefs identified as social cynicism and reward for application moderate the relationship between employees' work-related experiences, perceptions of CSR, attitudes, and behavioral intentions toward their firm. Utilizing a sample of 130 retail employees, we find that CSR affects more positively employees low on social cynicism and reduces distrust more so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 78 publications
(105 reference statements)
3
10
0
Order By: Relevance
“…Furthermore, company's employees seemed to respond positively to CSR activities and increase their confidence to their employer. Thus, benefits in this area derive by the improved relationship and increased trust between company and its employees, which, subsequently affects, positively, individual and organizational performance (West, Hillenbrand, and Money 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, company's employees seemed to respond positively to CSR activities and increase their confidence to their employer. Thus, benefits in this area derive by the improved relationship and increased trust between company and its employees, which, subsequently affects, positively, individual and organizational performance (West, Hillenbrand, and Money 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies demonstrated that the consequences of organizational cynicism might manifest themselves by passive participation in the activities of the organization, poor performance, low level of morals, and high absenteeism (Johnson, O'Leary-Kelly, 2003). There are also many studies that prove that cynicism has a negative impact on employees' loyalty, motivation and teamwork continuity (Ozer et al, 2014), since cynical employees do not trust others, they are less helpful (Kim et al, 2009;West et al, 2015;Terzi, Derin, 2016;Collins, 2017;etc. ).…”
Section: The Causes Of Organizational Cynicism and Its Consequences Fmentioning
confidence: 99%
“…In the specific case of retailers, and besides customers, one additional critical stakeholder must be employees, as "internal customers", to the extent that a socially responsible behavior to them regarding recruitment, remuneration, training, equality, health, retirement, work-life balance, and so on, [47] can help attract and retain high quality employees, increase their sense of identification with the firm and improve their relationships with consumers [47,48,77]. Similarly, the relationship and collaboration between retailers and suppliers plays a critical role in fostering sustainability [78], inasmuch as if retailers send signals of socially responsible behavior concerning their suppliers (from increasing the supplier education regarding sustainability issues [78] to promoting better wages, working conditions, and health and safety issues in third world suppliers [79], these behaviors can encourage consumers' expectations regarding the quality and value of the offer and boost the final market demand [80].…”
Section: Csr-related Drivers Of Online Voluntary Transparencymentioning
confidence: 99%